MULTI KULTURALISME AKAR RUMPUT Analisis terhadap Pandangan Anggota Majelis Taklim Aisyiah Kota Padang - Rais, Za'im (Universitas Islam Negeri Imam Bonjol Padang, 2019)
For centuries multiculturalism has been part and parcel of Minangkabau tradition. It colours and shapes every aspect of life of the Minangkabau society. This study attempts to explore how members of an Aisyiah Padang Branch Majelis Ta’lim view multicularism and how they reflect it in turn in social life. Multiculturalism in this study is defined limitedly as a religious group’s view over the existence of the other religious schools and the different religious groups. It is important therefore to examine in more details the Aisyiah Majelis Ta’lim members’ perspective over the existence of different religious schools and different religious groups. Based on this analysis, it is also urgent to disclose how the members tolerate and pay due respect to those different religious schools and different religious groups. Finally, the study seeks to elaborate the members’ attitude in building interaction and cooperation in social life among different religious schools and different religious groups. Qualitative approach is used in this research, data is mainly collected through depth interview with members of the Aisyiah Majelis Ta’lim. This research shows that, according to the Aisyiah Mejelis Ta’lim members, differences in religious interpretations and religious groupings are inevitably very natural. While doing their best to always defend carefully their own interpretation and belief, in social life they feel welcome to those different groups. In their opinion, differences in religious interpretations and groupings must always be tolerated and respected. Interaction and cooperation among different religious schools and religious groupings in social life, according to the members, is also necessary.